Arah Baru dalam Memahami Hadis tentang Khitan Perempuan - Delia, Yuli; Hidayat, Muhammad (Borneo : Journal of Islamic Studies, 2025)
This research aims to understand the hadiths discussing female circumcision from a historical perspective and the sciences (medicine). This approach is multidisciplinary, combining critical traditional methodology with anthropological, historical, and gender studies perspectives. This research systematically analyzes the chain of narrators (sanad) and content (matan) of key hadiths that are often potentially distorted, cultural biases, and the influence of socio-political interests at the time the hadiths were narrated and decodified. Furthermore, this research traces the historical roots of female circumcision practices in various ancient civilizations, including Egypt, Africa, and the Arabian Peninsula, to understand how this practice has evolved and adapted over time. A comparative analysis is conducted on the views of various schools of thought (mazhab) in Islamic jurisprudence (fiqh) regarding female circumcision, with the aim of uncovering interpretations and arguments that underlie these views. This study concludes that female circumcision in Islam is more appropriately understood as a cultural practice that has been Islamized, rather than a shar‘i obligation based on authentic hadith.